(untitled) (Global Journal of Management and Business Research, 2017)
Aim: The purpose of this article is to evaluate the role and contribution of procurement function in achieving firm#x2019;s competitive advantage within the value chain model whilst also retaining the fundamental principles and philosophy of the Porter#x2019;s value chain system. Background: In the increasingly globalised world it is important to conduct business activities that produce a value-based good or service. In a largely globalised commercial environment, the products and services would be homogenous to a large extent. The effects of globalisation have caused substantial changes in the business and commerce operations. The conventional view to conduct business operations has undergone a paradigm change. Hence, it is essential that the fundamental principles that have been established with regards to the conduct of production and service are also revisited in order to assess the need to redefine certain elements of the established business principles.